1981
DOI: 10.1017/s0021859600034675
|View full text |Cite
|
Sign up to set email alerts
|

Direct estimation of the extent of contamination of food residues by microbial matter after incubation within synthetic fibre bags in the rumen

Abstract: The artificial fibre bag technique has been widely used in studies of forage dry-matter digestibility (Van Keuren & Heinemann, 1962) and of the release of a range of plant constituents during fermentation in the rumen (Playne, McLeod & Dekker, 1972). More recently, the technique has been promoted as a simple means of estimating the rate and extent of food protein degradability in the rumen (θrskov & Mehrez, 1977; Mathers, Horton & Miller, 1977).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
35
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 6 publications
8
35
0
Order By: Relevance
“…As previously observed [9,16,34], the microbial contamination of FM was very low. This fact, together with the higher concentrations of amino acids in crude protein in FM than in SAB, showed that amino acid corrections from microbial contamination were practically null for this feed.…”
Section: Discussionsupporting
confidence: 82%
“…As previously observed [9,16,34], the microbial contamination of FM was very low. This fact, together with the higher concentrations of amino acids in crude protein in FM than in SAB, showed that amino acid corrections from microbial contamination were practically null for this feed.…”
Section: Discussionsupporting
confidence: 82%
“…The bags were incubated in two incubation series, on different days, for periods of 2, 4, 8, 16 and 24 h. All the bags of each incubation series were placed simultaneously in the rumen just before animals were offered the first meal of the morning (9:00 h). The specifications of the bags and incubations are in agreement with those of the INRA (14,9 vs. 20,8 % ; P < 0,01), pendant que la fraction insoluble potentiellement dégradable a résultée similaire (79,0 vs. 79,2 %). Au contraire, le taux de dégradation a été supérieur pour les AAT (11,5 vs. 8,4 % .…”
Section: Methodssupporting
confidence: 72%
“…This technique is also the most currently used to study amino acid degradation. However, true degradation values are always biased by the microbial contamination of incubated feed residues [4,14].…”
Section: Introductionmentioning
confidence: 99%
“…A great source of error with this method is the microbial contamination of feed particles within the artificial fibre bags, which results in an underestimation of CP degradation (Mathers and Aitchison, 1981;Südekum, 2005). Only few studies for quantifying this microbial contamination have been carried out and most in situ estimates of ruminal CP degradation simply neglect this microbial contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Mehrez and Ørskov (1977) used diaminopimelic acid (DAPA), Mathers and Aitchison (1981) 35 S, and Varvikko and Lindberg (1985) 15 N and DAPA as microbial markers.…”
Section: Introductionmentioning
confidence: 99%